Analysis of Relationship Between Employee Satisfaction and Job Performance in the Accommodation Sector - Arceli Romasanta (ASEAN Journal on Hospitality and Tourism, 2021)
Herzberg’s two-factor theory of motivation was employed in this study to analyze elements linked with job satisfaction and performance among employees in the accommodation sector. The researcher employed the descriptive-correlational methods of research, through questionnaires. The survey tool was validated by experts in the field of education, statistics and research and is highly accepted in terms of a Cronbach α of 0.988 which indicated an excellent index of reliability. Weighted Mean and Goodman and Kruskal’s Gamma Correlation determined the relationships between variables. The results revealed that employee satisfaction among employees was an important aspect that affected job performance and organizational success. Based on the findings, a Human Resource Plan is necessary to help increase satisfaction and improve job performance resulting in increased efficacy, self-esteem, and commitment in the accommodation sector. This paper would be extremely useful to human resource professionals, managers, owners, employees, and future researchers.